THE PATTERN OF OSTEOSARCOMA IN SOUTHERN PART OF IRAQ - LAMIA JARRALLAH (Basrah Journal of Surgery, 2007)
Osteosarcoma is a malignant tumor of mesenchymal cells characterized by the direct formation of bone or osteoid tissue by the proliferating malignant tumor cells. Grading of tumor is a good prog¬nostic indicator. It constitutes a basic factor of the current Enneking osteosarcoma staging system. The detection and identification of markers able to differentiate a high from a low malignant osteosarcoma which would substantially help the diagnosis, the prognosis and consequently the therapeutic approach of these tumors. This study is aimed to determine: The contribution of osteosarcoma to the total number of the malignant bone tumors registered in Basrah during the period of the study. The various histological subtypes and grades of osteosarcoma. A total number of thirty-seven cases of osteosarcoma diagnosed during the period 2000-2004 inclusive were collected from private and governmental hospital histopathological labrotaries in Basrah province. Clinical data concerning the age, sex, clinical presentations, radiological fea-tures and gross appearance of affected bone were evaluated. Histological sections of 25 out of 37 cases, were collected, re-evaluated and grades. Osteosarcoma was the most common primary malignant tumor of bone classified according to the tumor matrix into histological subtypes and analyzed for histological accounting for 35.92% of the primary malignant and 20.55% of the total malignant bone tumors. Of these 37 osteosarcoma cases, 35 (94.59%) were intramedullary and 2 (5.40%) were parosteal surface osteosarcoma. The male to female ratio was 1.1:1. The second decade was the most common age group of occurrence accounting for 23 out of 37 cases (62.2%). The main presenting clinical features were painless swelling recorded in 51.4%.The distal end femur, proximal end tibia and proximal end humerus were the most common sites of affection accounting for 27.02%, 32.43%, 16.21% respectively. The most common subtypes of osteosarcoma was osteoblastic (52%) followed by fibroblastic (Osteosarcoma 24%) and chondroblastic (20%); while telangiectatic subtypes was rare (4%). Parosteal osteosarcoma was a rare variant in our locality and other variants were not diagnosed during the period of the study. The majority of osteosarcoma cases (76%) were of grade III, followed by grade II (16%) and grade I (8%).